2007
DOI: 10.1016/j.str.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Signal Triggering in a gp130-Receptor Complex

Abstract: Summarygp130 is a shared signal-transducing membrane-associated receptor for several hematopoietic cytokines. The 30 Å resolution cryo-electron microscopy (cryo-EM) structure of the Interleukin 11(IL-11)-IL-11 Receptor-gp130 extracellular complex reveals the architecture and dynamics of this gp130-containing signaling complex. Normal-mode analysis reveals a repertoire of conformational changes that could function in signal triggering. This suggests a concerted mechanism of signaling involving all the component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 41 publications
3
59
0
Order By: Relevance
“…3, with contacts mediated by residues within domain 1 of gp130 and present in the flexible loop between helices S2 and D of IL-6 and in helix S1 (6). Interestingly, the surface of gp130 domain D1 involved in binding to IL-6/IL-6R␣ is shared by IL-11, which appears to form a similar hexameric signaling complex (29,30). This site is also used by a functional homolog of hIL-6 from Kaposi sarcoma-associated herpesvirus (viral IL-6), which in contrast to IL-6 has no requirement to interact with IL-6R␣ and signals via formation of a tetrameric viral IL-6/gp130 complex (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…3, with contacts mediated by residues within domain 1 of gp130 and present in the flexible loop between helices S2 and D of IL-6 and in helix S1 (6). Interestingly, the surface of gp130 domain D1 involved in binding to IL-6/IL-6R␣ is shared by IL-11, which appears to form a similar hexameric signaling complex (29,30). This site is also used by a functional homolog of hIL-6 from Kaposi sarcoma-associated herpesvirus (viral IL-6), which in contrast to IL-6 has no requirement to interact with IL-6R␣ and signals via formation of a tetrameric viral IL-6/gp130 complex (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these ligand-occupied receptor complexes consist of a a-receptors (IL6Ra, IL11Ra, CNTFRa, and CT1Ra) and signal-transducing b-receptors (GP130, LIFR, OSMR, IL27R/WSX-1, and IL31R/GPL), although LIF, OsM, and IL31 appear to from complexes comprising b-chains only (9). Binding of IL11 or IL6 to their respective ligandspecific a-receptors subunits results in sequential assembly with GP130 to form trimers with a geometry facilitating a cooperative transition into high-affinity, signaling-competent hexameric complexes comprising a 2:2:2 ratio of ligand, a-receptor and GP130 (13).…”
Section: Introductionmentioning
confidence: 99%
“…Low resolution electron microscopy (EM) images showed that the legs approach each other close to the membrane in a number of signaling-competent gp130 complexes (5,13,14). It has also been established by mutagenesis that the legs of the receptor provide an essential geometry required for signaling (15)(16)(17).…”
mentioning
confidence: 99%